The stratification of media usage in Finland, 2007–2018: Signs of socio-political polarization? - Heikkilä, Riie; Leguina, Adrian; Purhonen, Semi (New media & society, 2022)
Over the last 10–15 years, Western societies have faced two interrelated social changes: the digitalization of media and the increase in socio-political polarization. While their relationship is causally reciprocal, population-level empirical studies focusing on over-time change remain scarce. We adopt the temporal perspective on the socio-political stratification of media usage in the context of Finland, one of the so-called Nordic media welfare states. We ask whether the ways in which media usage is socially stratified has changed from 2007 to 2018 and whether there is political polarization of media consumption. We draw on two nationally representative comparative surveys, collected in 2007 (N = 1388) and 2018 (N = 1425), and show that the main media usage patterns—the wide, the narrow, and the Internet-focused media repertoires—differ both in terms of their sociodemographic and political profiles and that the opposition between the wide and the narrow repertoires becomes increasingly polarized.